2015
DOI: 10.3109/07420528.2015.1048867
|View full text |Cite
|
Sign up to set email alerts
|

Shift work and serum 25-OH vitamin D status among factory workers in Northern Italy: Cross-sectional study

Abstract: Low levels of vitamin D are related to muscle weakness, poor balance, and higher risk of falls, and can therefore have a major impact on performance and safety at work. Little knowledge exists on the association between work environment and vitamin D status. This study evaluates vitamin D status in shift workers. In this cross-sectional study, led during early springtime, 96 male shift workers at an engineering factory in Northern Italy, and 100 male daily workers operating nearby, participated. 25-OH vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…However, no significant difference in serum 25OHD levels was found between the night and day male workers, while the female night workers had lower serum 25OHD levels compared to the female day workers. This result was consistent with previous findings [43][44][45][46]. Ward et al have reported that night work was associated with low 25OHD levels in females but not in males [43].…”
Section: Vitamin D Deficiency and Night Shift Work O R I G I N A L P supporting
confidence: 83%
See 1 more Smart Citation
“…However, no significant difference in serum 25OHD levels was found between the night and day male workers, while the female night workers had lower serum 25OHD levels compared to the female day workers. This result was consistent with previous findings [43][44][45][46]. Ward et al have reported that night work was associated with low 25OHD levels in females but not in males [43].…”
Section: Vitamin D Deficiency and Night Shift Work O R I G I N A L P supporting
confidence: 83%
“…Ward et al have reported that night work was associated with low 25OHD levels in females but not in males [43]. In addition, Olivieri et al and Romano et al have found that significantly low 25OHD levels were shown in night workers compared to day workers [44,46]. On the other hand, a Korean study has shown that male, but not female, night workers had significantly lower 25OHD levels compared to day male workers [45].…”
Section: Vitamin D Deficiency and Night Shift Work O R I G I N A L P mentioning
confidence: 99%
“…[ 26 ] showed prevalence of vitamin D deficiency among the office workers (88.1%), higher than that of the manufacturing workers (79.0%). Romano et al [ 27 ] evaluates vitamin D status in shiftworkers at an engineering factory in Northern Italy, and 100 male daily workers operating nearby, 25-OH. Vitamin D levels were lower in shiftworkers than daily ones (13.4 ± 5.3 ng/mL versus 21.9 ± 10.7 ng/mL, p50.001).…”
Section: Resultsmentioning
confidence: 99%
“…It is also relevant to examine levels in respect of different seasons to confirm findings. In this study, vitamin D3 levels of workers on fixed night shifts were compared to those who work fixed daytime shifts, not in the summer but in winter when access to ambient UVB was not possible [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low vitamin D levels are discussed as possible effect modifying or mediating factor on cancer risk (16,20). A recent survey from Italy identified lower vitamin D levels among 96 shift workers as compared to 100 workers engaging in regular daily shifts (31). We studied the influence of vitamin D-deficiency on the association between shift/night work and prostate cancer but found that low vitamin D-levels at baseline had no effect modifying effect.…”
Section: Shift Work and Prostate Cancermentioning
confidence: 97%